2006
DOI: 10.1038/nm1450
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive volumetric optical microscopy in vivo

Abstract: Comprehensive volumetric microscopy of epithelial, mucosal and endothelial tissues in living human patients would have a profound impact in medicine by enabling diagnostic imaging at the cellular level over large surface areas. Considering the vast area of these tissues with respect to the desired sampling interval, achieving this goal requires rapid sampling. Although noninvasive diagnostic technologies are preferred, many applications could be served by minimally invasive instruments capable of accessing rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
320
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(322 citation statements)
references
References 28 publications
1
320
0
1
Order By: Relevance
“…57 and 58 demonstrated 19.6 µm and 15.7 µm transverse resolutions, respectively), and an SNR of 29 dB from a 3-µm diameter microsphere illuminated by a pulse energy of 500-nJ in a 9.2 µm beam diameter. As shown in the in vivo and ex vivo image demonstrations, the major benefit of the OR-PAEM over existing IVM techniques [44][45][46][47][48][49][50][51][52][53][54][55][56] lies in its label-free angiographic imaging capability, which provides critical image in experimental biology and clinical medicine. Although other groups [57,58] developed endoscopic devices with optical focusing and achieved an even smaller probe diameter (i.e., ~1.1 mm in the case of ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 and 58 demonstrated 19.6 µm and 15.7 µm transverse resolutions, respectively), and an SNR of 29 dB from a 3-µm diameter microsphere illuminated by a pulse energy of 500-nJ in a 9.2 µm beam diameter. As shown in the in vivo and ex vivo image demonstrations, the major benefit of the OR-PAEM over existing IVM techniques [44][45][46][47][48][49][50][51][52][53][54][55][56] lies in its label-free angiographic imaging capability, which provides critical image in experimental biology and clinical medicine. Although other groups [57,58] developed endoscopic devices with optical focusing and achieved an even smaller probe diameter (i.e., ~1.1 mm in the case of ref.…”
Section: Discussionmentioning
confidence: 99%
“…OR-PAM realizes the key benefits of PAT in biological experimentation through its high-resolution imaging capability; further, its unique optical absorption-based contrast mechanism enables it to complement conventional highresolution microscopy tools, such as confocal microscopy [44][45][46][47][48][49], two-photon microscopy [44][45][46][50][51][52][53], and optical coherence tomography [44][45][46][53][54][55][56]. So far, considerable efforts have been made to improve the spatial resolution [15], scanning speed [7,12], and functional imaging capability [4][5][6][7][8][9] of OR-PAM.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, research continues to eliminate the risk of ischemia completely, for instance by matching the refractive index of the blood serum with that of the red blood cells [199] or by using oxygen-carrying flushing liquids [200,201]. An important step was the introduction of high-speed FD-OCT systems, since it enabled the acquisition of large sampling volumes during relatively short flushing periods [36,195].…”
Section: Cardiologymentioning
confidence: 99%
“…The development of Fourier domain detection techniques and high speed, wavelength swept light sources has greatly improved the imaging speed and detection sensitivity of OCT systems, enabling volumetric endoscopic OCT imaging [10,11]. Using a high speed, wavelength swept light source based on a polygon mirror filter [12], early studies demonstrated volumetric endoscopic OCT of the esophagus and coronary arteries in living swine at an A-scan rate of 64 kHz [10]. In parallel, studies also demonstrated volumetric imaging in the rabbit GI tract using a high speed endoscopic OCT system with a Fourier domain mode-locked (FDML) laser at an A-scan rate of 100 kHz [11].…”
Section: Introductionmentioning
confidence: 99%